Fe3O4/Carbon Hybrid Nanoparticle Electrodes for High‐Capacity Electrochemical Capacitors. Issue 6 (6th April 2014) - Lee, Jun Seop; Shin, Dong Hoon; Jun, Jaemoon; Lee, Choonghyeon; Jang, Jyongsik
Abstract Fe3O4/carbon hybrid nanoparticles (FeCHNPs) were fabricated using dual‐nozzle electrospraying, vapor deposition polymerization (VDP), and carbonization. FeOOH nanoneedles decorated with polypyrrole (PPy) nanoparticles (FePNPs) were fabricated by electrospraying pristine PPy mixed with FeCl3 solution, followed by heating stirring reaction. A PPy coating was then formed on the FeOOH nanoneedles through a VDP process. FeCHNPs were produced through carbonization of PPy and FeOOH phase transitions. These hybrid carbon nanoparticles (NPs) were used to build electrodes of electrochemical capacitors. The specific capacitance of the FeCHNPs was 455 F g−1, which is larger than that of pristine PPy NPs (105 F g−1) or other hybrid PPy NPs. Furthermore, the FeCHNP‐based capacitors exhibited better cycle stability during charge–discharge cycling than other hybrid NP capacitors. This is because the carbon layer on the Fe3O4 surface formed a protective coating, preventing damage to the electrode materials during the charge–discharge processes. This fabrication technique is an effective approach for forming stable carbon/metal oxide nanostructures for energy storage applications.